Case report: Diagnosis of ADCY5-related dyskinesia explaining the entire phenotype in a patient with atypical citrullinemia type I - Pontrucher, Audrey; Barth, Magalie; Ziegler, Alban; Chao de la Barca, Juan Manuel; Mirebeau-Prunier, Delphine; Reynier, Pascal; Homedan, Chadi (Frontiers in Neurology, 2023)
We report here the case of a 13-year-old female patient with citrullinemia type 1 (MIM #215700), an autosomal recessive inherited disorder of the urea cycle, confirmed by the identification of a homozygous pathogenic variant in the ASS1 (argininosuccinate synthetase 1) gene. However, the patient presented abnormal hyperkinetic movements with global developmental delay, and clinical signs that were not fully consistent with those of citrullinemia type 1 or with those of her siblings with isolated citrullinemia type 1. Exome sequencing showed the presence of a de novo heterozygous pathogenic variant in the ADCY5 (adenylate cyclase type 5) gene. The latter confirmed the overlap with the so-called ADCY5-related dyskinesia with orofacial involvement, autosomal dominant (MIM #606703), a disorder disrupting the enzymatic conversion of adenosine triphosphate (ATP) to cyclic adenosine monophosphate (cAMP). The identification of this second disease led to the introduction, in addition to the citrullinemia-related low protein diet and arginine supplementation, of a treatment with caffeine which considerably improved the dyskinesia neurological picture. In conclusion, this case alerts to the importance of clinical-biological confrontation for the interpretation of genetic variants, as one hereditary metabolic disease may hide another with therapeutic decision consequences.